Pulmonary Hypertension: Let’s Take Stock! - Michele Cacia; Egidio Imbalzano; Vincenzo Antonio Ciconte; Marco Vatrano (Life)
Pulmonary hypertension (PH) encompasses a group of conditions characterized by elevated pulmonary arterial pressure, with pulmonary arterial hypertension (PAH) representing a distinct and severe subset. This review provides a comprehensive overview of the current classification system, highlighting the five clinical groups of PH and the specific hemodynamic criteria defining PAH. We discuss the complex pathophysiological mechanisms underlying PAH, including vascular remodeling, endothelial dysfunction, and genetic predisposition. Advances in diagnostic approaches are explored. Current treatment strategies targeting key molecular pathways such as endothelin, nitric oxide, and prostacyclin are reviewed alongside novel and investigational therapies. Prognostic indicators and risk stratification tools are evaluated to guide clinical management. Finally, we underscore the critical role of expert centers in accurate diagnosis, multidisciplinary care, and enrollment in clinical trials, which collectively improve patient outcomes in this challenging disease spectrum.